1986
DOI: 10.1161/01.hyp.8.11.1015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a difference in vitamin D metabolism between spontaneously hypertensive and Wistar-Kyoto rats.

Abstract: SUMMARY It has been contended that the metabolism of vitamin D in spontaneously hypertensive rats (SHR) is different from that in Wistar-Kyoto rats (WKY). To investigate this possibility, the plasma concentration of 1, 25-dihydroxycholecalciferol (1,25[OH] 2 D) and several known determinants of its production rate were measured in SHR and WKY given normal and restricted amounts of dietary phosphorus. In 12-week-old male SHR given a normal amount of dietary phosphorus, the mean plasma concentration of 1,25(OH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This study indicates that five times the standard cholecalciferol intake is sufficient to compensate for 25-OHD 3 loss when rats are fed 3% salt (three-times the standard salt intake) for 28 days. Spontaneously hypertensive rats have normal plasma 25-OHD concentrations [3,35,36], so decreased plasma 25-OHD concentration may be specific to salt-induced hypertension. Studies on humans have indicated an inverse relationship between plasma 25-OHD concentration or UVB light exposure and blood pressure [14,37].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that five times the standard cholecalciferol intake is sufficient to compensate for 25-OHD 3 loss when rats are fed 3% salt (three-times the standard salt intake) for 28 days. Spontaneously hypertensive rats have normal plasma 25-OHD concentrations [3,35,36], so decreased plasma 25-OHD concentration may be specific to salt-induced hypertension. Studies on humans have indicated an inverse relationship between plasma 25-OHD concentration or UVB light exposure and blood pressure [14,37].…”
Section: Discussionmentioning
confidence: 99%
“…- 43 The reason for these discrepancies in hypertensive humans is unclear but may relate to dietary or age differences of the subject groups between studies. Our results support the observations of elevated 1,25(OH) 2 D 3 in some older populations of essential hypertensive men.…”
mentioning
confidence: 99%
“…8 The 25-OH-D concentration decreased with the feeding of a low calcium diet in both strains, but remained greater in SHR than in WKY. 8 In studies by others, 25-OH-D was found to be elevated 20 or the same 1 0 2 1 2 2 in the SHR as compared with the WKY. Thus, the findings of the present study with animals from different breeders reflect these published data: 25-OH-D concentration is dependent on breeder and age of animal.…”
Section: Resultsmentioning
confidence: 87%